2003
DOI: 10.1525/si.2003.26.3.381
|View full text |Cite
|
Sign up to set email alerts
|

Displacement and Identity Discontinuity: The Role of Nostalgia in Establishing New Identity Categories

Abstract: I examine how displacement affects identity continuity by studying the disruption experienced by a group of employees when their organization moved to a new site. Data on the organization (a university campus restaurant known as the "Coffee House") included participant observation and interviews. I argue for the importance of examining identity continuity and discontinuity in relation to specific interactional experiences in and attachment to the built environment. I expand on the analysis of nostalgia as a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
165
2
8

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(179 citation statements)
references
References 45 publications
4
165
2
8
Order By: Relevance
“…Nostalgia appears as a useful tool to help people reinforce their collective and individual identity because it ties them to history through context (Milligan, 2003). Many MLB and NFL franchises created interactive entertainment zones, considered various architectural considerations, and embraced several different structures to help promote this connection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nostalgia appears as a useful tool to help people reinforce their collective and individual identity because it ties them to history through context (Milligan, 2003). Many MLB and NFL franchises created interactive entertainment zones, considered various architectural considerations, and embraced several different structures to help promote this connection.…”
Section: Resultsmentioning
confidence: 99%
“…The study of nostalgia is limited despite the fact that many political and economic figures and organizations exploit it to their advantage (Brown & Humphreys, 2002;Gabriel, 2000;Hinch & Higham, 2004;Milligan, 2003;Ritchie & Adair, 2004;Strangleman, 1999Strangleman, , 2002. For instance, marketing and consumer behavior scholars noted organizations use nostalgia to motivate or prompt the use of specific products and services and as a tool to positively affect brand image (Funk & James, 2006;Goulding, 2001;Havlena & Holak, 1991, 1998Holbrook, 1993;Moriarty & McGann, 1983;Pascal, Sprott, & Muehling, 2002;Unger, McConocha, & Faier, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, experimental studies have shown that people who were asked to recall nostalgic experiences report a heightened perception of continuity between their past and present selves compared with people who were asked to recall ordinary experiences (Routledge et al, 2006). Qualitative analyses of organizational change also suggest that nostalgia allows individuals to develop a sense of identity continuity (Brown & Humphreys, 2002;Milligan, 2003).…”
Section: Explaining the Positive Consequences Of Nostalgia: Identitymentioning
confidence: 99%
“…Carsten & Hugh-Jones, 1995;Fox, 1993;Waterson, 1990) that illustrate how architectural forms and their configuration represent enduring and significant repositories of knowledge and cultural meaning (McWilliams, 2005, p. 29). Anthropologists have been interested in the affective attachments that link people to place, the ways rooms, buildings and land are endowed with emotional meaning, and the aspects of individual identity that have a desire for, memory of, and emotional attachment to, a physical setting (Hochschild, 2010;Milligan, 2003). The link between architecture and anthropology is, however, not singular and there has been a mutual interest of anthropological discourses within architectural domains.…”
Section: Introductionmentioning
confidence: 99%